The effects of phosphorus and humic acid on some soil properties flowers quality of Gladiolus - Çavuşoğlu, Mehmet Nuri; Türkoğlu, Nalan; Özdemir, Fethi Ahmet (Progress in Nutrition, 2017)
This study was conducted to determine the effects of various phosphorus and humic acid applications on the development of gladiolus varieties in pot culture. This study was carried out between May 2014 and April 2015. Rose Supreme, Red, and Essential cultivars were grown in soiled pods with 0, 100, 200 mg/kg phosphorus and 0, 1000, 2000 mg/kg humic acid doses. We found that application of humic acid and phosphorus had positively contributed to N and P contents in the soil as well as floret number of gladiolus and flower-stalk length. As a result of the study, optimum doses were determined as 2000 mg/kg humic acid and 200 mg/kg  phosphorus with regard to the studied characteristics.